Industry 4.0 Retrofitting - Lins, Theo; Oliveira, Ricardo R.; Correia, Luiz Henrique; Silva, Jorge Sa (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2018)
Industry 4.0 or Fourth Industrial Revolution is a new concept which involves technological innovations applied in industrial processes. Using technologies such as Internet of Things, Cyber-Physical Systems and cloud computing, industries tend to become more efficient, autonomous and customizable. However, migration process to Industry 4.0 is not instantaneous, as it depends on the economic and technological investments in the industries of each country. In many countries, industries have not reached the Third Industrial Revolution yet and do not have many investments in the industrial sectors, which creates a challenge to modernize existing industries. From this challenge, an alternative to take off to Industry 4.0 with low cost and agility is known as retrofitting, which is the reuse of old equipment and the integration of new Technologies simultaneously. In this paper is proposed, a way of performing the retrofitting process for Industry 4.0, through a platform that, regardless the model or type of the industrial equipment, offers resources to integrate this equipment with Industry 4.0. To implement the platform, requirements and technologies necessary to perform retrofitting for Industry 4.0 were defined. Afterward, the methods usage in the platform were presented. To validate the operation of the platform a case study with a didactic plant of an automated industry was carried out and as a result the impact after retrofitting for Industry 4.0 is shown.